The Difference of Endometrial Leptin Expression in Woman with Polycystic Ovarian Syndrome (PCOS) Compared to Normal - Besar, Dwi Sakti Berlian; Budihastuti, Uki Retno; Sulistyowati, Sri; Melinawati, Eriana (Indonesian Journal of Medicine, 2020)
Background: Decreased endometrial receptivity is suspected to be one of the factors causing infertility in women with Polycystic Ovary Syndrome (PCOS). Endometrial abnormalities in PCOS due to impaired balance include estrogen, progesterone, growth factors, cytokines and cell attachment modulators including leptin. This study aims to determine the expression of leptin in the endometrium which is suspected to be more common in PCOS patients and related factors.Subjects and Method: A retrospective-case control study was conducted at Dr. Moewardi general hospital, Surakarta. A total of 60 women were involved; 30 infertile women with PCOS based on Rotterdam criteria (if found two of the three symptoms, including hyperandrogenism, ovulation dysfunction and/or polycystic ovaries from ultrasonography) and 30 normal women as control group. Demographic data such as age, family history of PCOS, menarche, BMI, occupation, and education were recorded. Leptin expression was acquired from endometrium biopsy with IHC examination on day 19-24 of the menstrual cycle; under the condition that inclusion and exclusion criteria are fulfilled. The statistical analysis was performed using the Mann-Whitney test.Results: Mean of leptin expression was found significantly higher in PCOS group (Mean= 59.16; SD= 49.34) compared to control group (Mean= 6.00; SD= 22.98, with p= 0.001. PCOS (b= 0.42; 95% CI= 0.10 to 0.73; p= 0.010) and obesity (b= 0.31; 95% CI= 0.41 to 0.58; p= 0.025) increased leptin expression.Conclusion: There is a difference in leptin expression in the endometrium of PCOS compared to normal.  Leptin expression is higher in the endometrium of women with PCOS and obesity compared to normal.Keywords: Leptin expressions, endometrium, polycystic ovarian syndrome.Correspondence: Dwi Sakti Berlian Besar. Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi General Hospital, Surakarta, Indonesia. Email: dwiesakti@student.uns.ac.id. Mobile: +628121845054Indonesian Journal of Medicine (2020), 05(01): 38-46https://doi.org/10.26911/theijmed.2020.05.01.06